Quality management system in a peruvian public university: analysis of the main processes and risk management - Adriazola León, Ana María (2020)
An analysis of the quality management system of the Faculty of Sciences of a public university in Peru is presented. The objective was the identification, description, characterization and analysis of risks of the main processes of university management. Methodologically, the document review technique was used for diagnosis purposes, in addition, the ISO 9001:2015 STANDARD was used as a guide to identify, characterize processes, and carry out a risk analysis according to the process approach. The results made it possible to identify and describe the procedures and make a proposal for risk management of the main processes within the framework of the implementation of a quality management system.